Agricultural process engineering - Henderson, M. S. (Avi textbook, 1979)
The engineering approach - Fluid mechanics - Fluid-flow measurements - Pumps - Fans - Size reduction - Cleaning and sorting - Material handling - Heat transfer - Air-vapor mixtures (the psychrometric chart) - Drying - Refrigeration - Process condition observations, marc:records and controls - Cost analysis - Process analysis and plant design - Manual operation economy.